A companion to medieval Lubeck
1 online resource.
Keywords: A Companion to Medieval Lübeck offers an introduction to recent scholarship on the vibrant and source-rich medieval history of Lübeck. Focusing mainly on the twelfth to fifteenth centuries, the volume positions the city of Lübeck within the broader history of Northern Germany and the Baltic Sea area. Thematic contributions highlight the archaeological and architectonical development of a northern town, religious developments, buildings and art in a Hanseatic city, and its social institutions. This volume is the first English-language overview of the history of Lübeck and a corrective to the traditional narratives of German historiography. The volume thus offers a fresh perspective on the history of medieval Lübeck—as well as a handy introduction to the riches of the Lübeck archives—to undergraduates, graduate students, and scholars in related fields. Contributors are Manfred Finke, Hartmut Freytag, Antjekathrin Graßmann, Angela Huang, Carsten Jahnke, Ursula Radis, Anja Rasche, Dirk Rieger, Harm von Seggern and Ulf Stammwitz.